2007
DOI: 10.1016/j.brainres.2007.08.068
|View full text |Cite
|
Sign up to set email alerts
|

A prototypical Sigma-1 receptor antagonist protects against brain ischemia

Abstract: Previous studies indicate that the Sigma-1 ligand 4-phenyl-1-(4-phenylbutyl) piperidine (PPBP) protects the brain from ischemia. Less clear is whether protection is mediated by agonism or antagonism of the Sigma-1 receptor, and whether drugs already in use for other indications and that interact with the Sigma-1 receptor might also prevent oxidative damage due to conditions such as cerebral ischemic stroke. The antipsychotic drug haloperidol is an antagonist of Sigma-1 receptors and in this study it potently p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
58
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 49 publications
4
58
0
1
Order By: Relevance
“…Previous studies with tumor cells showed that 2 receptor activation causes ROS generation (Ostenfeld et al, 2005). 1 Receptors are involved in oxidative stress-mediated toxicities such as ischemic stroke and have been shown to provide protective effects (Schetz et al, 2007). Receptors also play a regulatory role in the redox state of cells and can modulate cellular NOS enzyme activity (Tsai et al, 2009;Yang et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies with tumor cells showed that 2 receptor activation causes ROS generation (Ostenfeld et al, 2005). 1 Receptors are involved in oxidative stress-mediated toxicities such as ischemic stroke and have been shown to provide protective effects (Schetz et al, 2007). Receptors also play a regulatory role in the redox state of cells and can modulate cellular NOS enzyme activity (Tsai et al, 2009;Yang et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Of the most prominent actions of Sig-1Rs or those ligands is their robust cellular protective effect (Maurice and Lockhart, 1997;Bowen, 2000). Sig-1R agonists have been shown to promote cellular survival by preventing oxidative stress caused by ischemia (Schetz et al, 2007), diabetes (Smith et al, 2008), inflammation (Wang et al, 2008), and ␤-amyloid toxicity (Meunier et al, 2006).…”
mentioning
confidence: 99%
“…Although m-and p-DTG showed similar potency relative to o-DTG, DPhG, which lacks the methyl moiety, produced a block statistically greater than the parent compound (P , 0.05) (Fig. 3B) Fluoro substitution of piperidine compounds has been shown to increase the lipophilicity of the molecules (de Candia et al, 2009), and several piperidine derivatives have long been used as s receptor ligands (Nakazawa et al, 1998;Schetz et al, 2007). Further experiments were conducted to evaluate whether methyl-to-fluoro substitution of o-DTG would result in increased drug potency.…”
Section: Resultsmentioning
confidence: 97%
“…Experiments were conducted to compare the capacity of DTG analogs to affect three important contributors to the demise of brain cells after ischemic stroke: intracellular Ca 21 dysregulation produced in neurons by (1) acidosis and (2) ischemia and (3) activation and migration of microglial cells. Although previous studies using guanidine substitutions were made in an attempt to characterize the structureaffinity relationships (Reddy et al, 1994;Schetz et al, 2007), our focus was to identify the effects that steric hindrance, electrostatic interactions, or increased lipid permeability had on the structure-activity relationship in mitigating increases in [Ca 21 ] i . p-BrDPhG showed the greatest block in inhibiting increase in [Ca 21 ] i evoked via ischemia or acidosis and in mitigating activation and migration of microglial cells.…”
Section: Introductionmentioning
confidence: 99%